Hubungan Persepsi, Pengaruh Teman Sebaya dan Dukungan Keluarga dengan Perilaku Merokok Remaja Laki-Laki - Sholihah, Hanifah; Novita, Astrid (Journal of Public Health Education, 2021)
Introduction: Smoking behavior in adolescents in Indonesia increased, in 2013 (7.9%), in 2016 (8.8%) and 2018 (9.1). Bogor regency became the location with the highest rate of teen smoking than West Java Province. The high prevalence of smokers in adolescents is influenced by perception, peer influence and family support. Objectives: The study aims to find out the relationship of perception, peer influence and family support with male adolescent smoking behavior.Method: This research method is quantitative using cross sectional design. The subject of this study was a male teenage smoker in Bogor Regency, sampling techniques using purposive sampling of as many as 100 respondents. Data analysis is conducted univariate and bivariate with chi square test. Result: Based on statistical tests, there are two variables that show a relationship i.e. perception (Pv = 0.005 and OR=3,431), peer influence obtained (Pv = 0.001 and OR=4,524 ), while there is one variable that indicates no relationship i.e. family support (Pv = 0.694), with male adolescent smoking behavior in Bogor Regency. Conclution: It is expected to be expected to promote health promotion related to the dangers of cigarettes, but use social media and work with influencers, as well as create a family empowerment concept teen smoker prevention program to prevent the initiation of smoking behavior. It aims to lower the number of teen smokers in Bogor Regency.